Comparison of long-term patient-reported outcome and quality of life 10 years after severe trauma versus polytrauma - Adelina Denzel; Annette Keß; Christian Kleber; Georg Osterhoff (PLoS ONE, 2026)
Purpose Severe trauma and polytrauma are major public health concerns due to their long-term impact on survivors’ quality of life (QoL). While advances in trauma care have improved survival rates, long-term functional, psychological, and social outcomes remain inadequately understood. This study evaluates the health-related quality of life (HRQoL), functional deficits, and mortality of trauma patients ten years post-injury, comparing severely injured (SI) and polytrauma (PT) patients. Methods Patients admitted to the shock trauma unit at a Level 1 trauma center between 2010 and 2013 with an Injury Severity Score (ISS) ≥ 9 were identified. Survivors were categorized into SI (ISS ≥ 9 and <16 or isolated injury in one body region) and PT (ISS ≥ 16 and injuries in multiple body regions). HRQoL was assessed using the Polytrauma Outcome (POLO) Chart, including the EuroQol 5D-3L, SF-36, and Trauma Outcome Profile (TOP). Results Ninety-one patients (42 SI, 49 PT) completed follow-up, with an additional 80 confirmed deceased patients. Polytrauma patients had significantly longer hospital and ICU stays, higher rates of mechanical ventilation, and worse functional outcomes (p < 0.001). While PT patients reported more physical impairments and pain (SF-36 Physical Functioning, Physical Role, and Pain dimensions; p < 0.05), no significant differences were observed in psychological or social dimensions. Overall, 60.4% of the cohort reported reduced QoL (EuroQol Index ≤0.8), with no significant difference between SI and PT groups. Long-term mortality did not differ between groups (p = 0.6). Conclusion Ten years post-trauma, both SI and PT patients experience substantial reductions in QoL, with physical impairments more pronounced in PT patients. However, psychological and social outcomes appear independent of injury severity, suggesting that factors beyond trauma severity influence long-term recovery. These findings highlight important associations relevant to long-term outcomes and underscore the need for further research to better define how persistent pain, functional limitations, and psychosocial factors interact in long-term recovery after severe injury and polytrauma.